Effect of rainfall infiltration on distribution of soil suction and slope stability [electronic resource] - Mohd. Fazli Zikiri, author; Fakulti Kejuruteraan Awam (2008)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2008